Domestic violence as a breach of fundamental human rights in Nigeria (2018)
In Nigeria, domestic violence is a problem that is not new in many parts of Africa. However, there is a deep cultural belief that it is socially acceptable to hit a woman to discipline a spouse regardless of the fact that there are laid down provisions in the law. It is widespread and it is seen as an act of intimidation, physical, verbal or emotional abuse that has become an epidemic and it occurs in all sectors of the society. When women are faced with this problem, most women grieve in pain and silence because there are no systems of law that can adequately protect their rights. In Nigeria, there is a federal law, Violence against Persons Prohibition Act (VAPP), 2015 which provides for violence against women but the law can only be used in FCT, Abuja but this law is not all encompassing. In addition, even though some states have enacted Domestic Violence legislations, it is not enough as it only takes care of four states. The paper will therefore discuss the incidents of domestic violence, its causes, the international laws of which Nigeria is a member and the way forward in alleviating the plight of women